A STUDY ON THE EUTROPHICATION OF THE ASAHI RIVER DAM RESERVOIR AND THE INFLUENCE OF DROUGHT ON WATER QUALITY - NAGO, Hiroshi; KAWARA, Osami; TAKASUGI, Shigeru; ABE, Fumihiro (ENVIRONMENTAL ENGINEERING RESEARCH, 1995)
In this case study on Asahi River Dam reservoir, we discussed the relationship between hydraulic retention time and increase of phytoplankton, and the propagation of water quality in the reservoir to the downstream. Since the observation time includes the severe drought period, the influence of the drought on the water quality is also discussed. Obsevations were carried out from spring to late autumn in 1993 and 1994 and the Observation points are located from upstream of the reservoir to the downstream. The water quality components observed are phosphorus, nitrate, chemical oxygen demand, chlorophyll-a. The water quality in the reservoir is different from the upstream to the downstream. The chlorophyll-a increases in the reservoir, but it often descreases in the downstream in spite of the sufficient nutrients. The particulate components of COD, nitrogen and phosphorus decrease during flow down. The hydraulic retention time is a limiting factor for increase of phytoplankton in the Asahi River Dam reservoir. A retention time of at least 2 to 3 weeks is necessary for the sufficient increase of phytoplankton. This retentin time can be predicted by the growth rate of phytoplankton. The water quality in the reservoir is not affected significantly by the draught since the hydraulic retention time and pollutant loads decreased.